A Ti3C2T-based x Multilayer wave-shaped terahertz wave super-absorbing material
Patent Information
- Application Number
- CN202310215763.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-03-08
AI Technical Summary
[0004]本发明的目的在于针对现有太赫兹吸波材料存在的阻抗匹配与衰减匹配的矛盾,以及制作成本高昂、制备过程繁复、应用稳定性不可靠等问题,提出一种结构稳定、超薄轻质及高吸收强度的基于Ti3C2Tx的多层波浪型太赫兹波吸收材料
[0022]1.本发明提供的基于Ti3C2Tx的多层波浪型太赫兹波超强吸收材料,采用高Ti3C2Tx负载量的织物层、低Ti3C2Tx负载量的织物层以及零Ti3C2Tx负载量的织物层的组合,解决了单一结构导致的阻抗匹配和高电损耗之间的矛盾;
Smart Images

Figure CN116423930B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic functional materials technology, and relates to electromagnetic wave absorption structures, specifically providing a structure based on Ti3C2T. x Multilayer wave-shaped terahertz wave super-absorbing material. Background Technology
[0002] Terahertz (THz) waves refer to electromagnetic waves in the frequency range of 0.1 to 10 THz (corresponding to wavelengths of 3 mm to 30 μm). Terahertz waves have many advantages, such as low radiation energy, strong penetration, good coherence, and wide bandwidth, making them extremely valuable in biomedicine, security detection, military stealth, and the upcoming 6G communication fields. With the deepening research of terahertz technology in various fields, the demand for high-performance terahertz absorbing materials is increasing. For example, in the field of terahertz radar detection, using materials with extremely strong absorption properties can significantly reduce the radar's cross-section, greatly enhancing its stealth capabilities. In the field of sixth-generation communication, high-performance absorbing materials are needed in terahertz transceivers to significantly reduce sidelobe radiation or clutter for stable signal transmission. In addition, terahertz absorbing materials can also significantly reduce electromagnetic radiation in the surrounding environment, playing a vital role in improving environmental quality and human health. Therefore, high-efficiency and low-cost terahertz absorbing materials are of great practical significance and value for the development and application of terahertz technology.
[0003] Currently, the design of electromagnetic absorbing materials should focus on two aspects: first, maximizing the penetration of electromagnetic waves into the material without reflection from its front surface (impedance matching); and second, ensuring that terahertz waves entering the material are rapidly absorbed and attenuated (attenuation matching). However, the material's conductivity becomes a limiting factor. Electromagnetic waves entering the material induce macroscopic currents; as conductivity increases, the current intensifies, and electromagnetic energy is converted into heat more quickly, achieving attenuation. However, due to the skin effect, when electromagnetic waves strike a material with high conductivity, a skin current forms, increasing reflectivity and reducing the matching degree between the material's electromagnetic parameters and the air, negatively impacting absorption. Therefore, absorbing materials with a single absorption structure require a trade-off, making it difficult to achieve optimal absorption. Building on this, in 2022, a team from Nankai University proposed a composite foam of graphene and polyaramid in the paper "Cheng Z. Interfacial π–π Interactions Induced Ultralight, 300℃-Stable, Wideband Graphene and Polyaramid Foam for Electromagnetic Wave Absorption in Both Gigahertz and Terahertz Bands". Its RLmin in the 0.2–1.6 THz frequency band was -17 dB, which is insufficient to meet the current high-performance requirements for microwave absorbing materials. In 2021, a team from Northwestern Polytechnical University proposed a multilayer microwave absorbing material in the paper "Zheng WX-band full absorbing multi-layer foam with lightweight and flexible performance. 2021". This material uses a three-layer structure of foam-film-foam, simultaneously considering impedance matching, dielectric loss, and destructive interference, achieving excellent electromagnetic wave absorption performance; however, the fabrication process is too complex and the preparation cost is high. Given the current problems of impedance matching and attenuation matching contradictions and low practical value of terahertz wave absorbing materials, there is an urgent need to develop a high-performance, low-cost, and highly applicable material for terahertz electromagnetic wave absorption. Summary of the Invention
[0004] The purpose of this invention is to address the contradictions in impedance matching and attenuation matching in existing terahertz absorbing materials, as well as the problems of high manufacturing costs, complex preparation processes, and unreliable application stability. This invention proposes a structurally stable, ultrathin, lightweight, and high-absorption-strength Ti3C2T-based terahertz absorbing material. xA multilayered wave-shaped terahertz wave absorbing material. This invention utilizes Ti3C2T x The high dispersibility of two-dimensional nanosheets in aqueous solution was leveraged to composite with flexible fabrics, resulting in the preparation of microwave absorbing fabrics with varying loadings. These fabrics were then bonded together using aqueous polyurethane as an adhesive, utilizing Ti3C2T... x The ultra-high conductivity of the material and the conductive network formed by the fiber structure of the fabric achieve excellent absorption strength, resulting in RL≤-22dB and RL0 in the frequency range of 0.3–1.2THz. min The absorption effect is approximately -48 dB; furthermore, this absorbing material possesses excellent properties such as strong mechanical properties, reliable application stability, and thinness. The sample thickness of this material is between 5 and 6 mm, and the mass density is 43 mg / cm³. 2 Meanwhile, this absorbent material also has many advantages such as low preparation cost, convenient preparation process and large-area preparation, and has excellent practical application value.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] A Ti3C2T-based x A multi-layered wave-shaped terahertz wave super-absorbent material, characterized in that the wave-shaped terahertz wave super-absorbent material is composed of a multi-layered fabric structure and an outer layer of water-based polyurethane (WPU), wherein the multi-layered fabric structure is composed of multiple layers of flexible fabric, and each layer of flexible fabric is adsorbed and filled with a corresponding loading amount of Ti3C2T. x Following the bottom-up order, Ti3C2T on the flexible fabric x The load decreases layer by layer until it reaches zero; the multi-layered fabric structure presents a wavy, undulating shape.
[0007] Furthermore, the flexible fabric includes, but is not limited to: cotton gauze, non-woven fabric, grey fabric, cleanroom cloth, etc.
[0008] Furthermore, the Ti3C2T-based x The preparation method of the multilayer wave-type terahertz wave super-absorbing material includes the following steps:
[0009] Step 1: Use an acidic etching solution to etch Ti3C2T x The precursor Ti3AlC2 was selectively etched, and the reaction product was centrifuged, washed, and freeze-dried to obtain multilayer Ti3C2T. x Powder; multilayer Ti3C2T x The powder was placed in an intercalation solution for intercalation treatment, and the reaction product was centrifuged and washed to obtain Ti3C2T. x The precipitate was then dispersed in deionized water to obtain a predetermined concentration of Ti3C2T. x suspension;
[0010] Step 2: Pre-clean and dry the flexible fabric with anhydrous ethanol to obtain a zero-load flexible fabric; immerse the flexible fabric in Ti3C2T x The fabric is placed in a suspension and rolled multiple times on both sides using rollers. After being removed, it is left to dry at room temperature to obtain a flexible fabric with a preset load.
[0011] Step 3: According to Ti3C2T x The load is gradually reduced from bottom to top until zero, and multiple layers of flexible fabric are stacked to form a multi-layer fabric structure.
[0012] Step 4: Immerse the multi-layered fabric structure in an aqueous polyurethane dispersion and roll it with rollers to remove air between the multiple layers of flexible fabric. After removal, fold it over and then let it dry at room temperature to obtain the Ti3C2T-based structure. x Multilayer wave-shaped terahertz wave super-absorbing material.
[0013] Furthermore, in step 1, the acidic etching solution is obtained by uniformly mixing hydrofluoric acid, hydrochloric acid and deionized water, wherein the mass percentage of hydrofluoric acid is 49 wt% and the mass percentage of hydrochloric acid is 38 wt%; the volume ratio of hydrofluoric acid, hydrochloric acid and deionized water is 5:12:24.
[0014] Furthermore, in step 1, the intercalation solution is obtained by mixing solid lithium chloride (LiCl) powder with deionized water, wherein 1g of lithium chloride powder is dissolved in every 40ml of deionized water.
[0015] Furthermore, in step 1, each 1g of precursor Ti3AlC2 corresponds to 20.5ml of etching solution; each 1g of precursor Ti3AlC2 corresponds to 40ml of intercalation solution.
[0016] Furthermore, in step 2, the dimensions of the flexible fabric are: length 50 ≤ mm, width 50 ≤ mm, and thickness 0.29 mm ≤ 0.32 mm.
[0017] Furthermore, in step 2, the number of single-sided rolling cycles is ≥10.
[0018] Furthermore, in step 4, the number of rolling cycles is ≥10, and the folding interval is 8-10mm.
[0019] In terms of working principle:
[0020] This invention provides a Ti3C2T-based x The multilayer wave-shaped terahertz wave super-absorbing material has a main structure of high Ti3C2T x Fabric layer with high load capacity, low Ti3C2T xThe fabric layer with load capacity and zero Ti3C2T x The multi-layered structure of the fabric layer with high load capacity exhibits an undulating, wave-like shape, and is coated with an extremely thin layer of waterborne polyurethane (WPU) to form the multi-layered structure. For a single-layer structure, low load capacity means that the Ti3C2T adhered to the fabric... x The Ti3C2T particles are relatively few in number and dispersed, resulting in fewer conductive paths. Terahertz wave incidence does not induce a significant skin effect, leading to good impedance matching and low reflectivity. However, this also limits their internal attenuation of terahertz waves. High load means that the Ti3C2T particles attached to the fabric... x While single-layer structures possess rich internal mechanisms for attenuating terahertz waves and offer excellent electrical losses, they also exhibit a significant skin effect on the surface, leading to high reflectivity and impedance mismatch. In summary, single-layer structures present a trade-off between impedance matching and efficient electrical losses. Multilayer structures, however, leverage the advantages of different single-layer structures. When incident terahertz waves reach the upper surface of the material, the extremely low conductivity of the WPU outer shell and the zero-load layer of the first layer makes the electromagnetic parameters of the material surface approximate those of air, achieving excellent impedance matching. This allows terahertz waves to enter the absorbing material with almost no reflection. Furthermore, compared to a flat shape, the wavy shape causes multiple reflections of the incident terahertz waves, reducing the overall reflectivity of the material and increasing the amount of terahertz waves entering the material. Once inside the absorbing material, the concentration between layers exhibits a variation trend, preventing significant impedance differences from affecting terahertz wave transmission. As for how the material attenuates the energy of the terahertz waves, one factor is the presence of Ti3C2T... x The extremely high electrical conductivity of the nanosheets, Ti3C2T attached to the fabric skeleton x The nanosheets form an excellent conductive network, and terahertz waves induce current to propagate on it. Some electromagnetic energy is converted into heat and lost, resulting in extremely high electrical losses for the terahertz waves. On the other hand, Ti3C2T... x Nanosheets can exist in three ways on fabric fibers: attachment, suspension, and film formation. Terahertz waves are present in these Ti3C2T nanosheets. x Multiple reflections and scatterings between nanosheets provide abundant propagation paths for terahertz waves, which gradually attenuate with each propagation. In summary, terahertz waves exhibit extremely strong attenuation within the absorbing material, achieving excellent absorption performance. Furthermore, the presence of waterborne polyurethane not only enhances the absorption of Ti3C2T... x The adhesion of nanosheets is greatly enhanced, avoiding the formation of Ti3C2T x The shedding of nanosheets during actual use also significantly improves the strength and hardness of the multilayer structure, ensuring the working stability of the microwave absorbing material in practical applications.
[0021] In summary, the present invention has the following beneficial effects:
[0022] 1. The invention provides a Ti3C2T-based... x Multilayer wave-shaped terahertz wave super-absorbing material, using high Ti3C2T x Fabric layer with high load capacity, low Ti3C2T x The fabric layer with load capacity and zero Ti3C2T x The combination of fabric layers with load capacity resolves the contradiction between impedance matching and high electrical loss caused by a single structure;
[0023] 2. The Ti3C2T-based invention provided by this invention x The multi-layered wave-shaped terahertz wave super-absorbing material uses a wave-like shape to change the reflection properties of terahertz waves on the surface, changing it from specular reflection to diffuse reflection, reducing the material's reflectivity to the outside world, and enhancing the material's absorption effect of terahertz waves.
[0024] 3. The Ti3C2T-based invention provided by this invention x The multilayered wave-shaped terahertz wave superabsorbing material exhibits broadband strong absorption characteristics, with RL ≤ -22dB and RL within the testing range of 0.3–1.2THz. min ≈-48dB;
[0025] 4. The present invention provides a method based on Ti3C2T x This multi-layered, wave-shaped terahertz wave superabsorbing material possesses lightweight physical properties, excellent mechanical properties, and application stability. It can be bent, stretched, vibrated, and shaken without exhibiting any resistance to Ti3C2T. x Shedding;
[0026] 5. This invention provides a method based on Ti3C2T x The multi-layered wave-shaped terahertz wave super-absorbing material has the advantages of simple manufacturing process and low preparation cost; at the same time, it has a wide range of applications, strong adaptability, and is feasible for large-scale production and use. Attached Figure Description
[0027] Figure 1 The invention is based on Ti3C2T x A schematic diagram of the main structure of a multi-layered wave-shaped terahertz wave super-absorbing material.
[0028] Figure 2 The invention is based on Ti3C2T x Physical images and reflection comparison diagrams of multilayered wavy and non-wavy terahertz wave super-absorbing materials.
[0029] Figure 3This is a structural strength test diagram of the multilayer wave-type terahertz wave super-absorbing material in an embodiment of the present invention.
[0030] Figure 4 These are scanning electron microscope test images of single-layer and multi-layer structures in embodiments of the present invention. Among them, (a) is a zero-load fabric, (b) is a low-load fabric, (c) is a high-load fabric, and (d) is a multi-layer structure.
[0031] Figure 5 This is a comparison diagram of the reflectivity of single-layer and multi-layer structures in an embodiment of the present invention.
[0032] Figure 6 This is a comparison diagram of the electromagnetic shielding effectiveness of single-layer and multi-layer structures in an embodiment of the present invention.
[0033] Figure 7 This is a comparison diagram of the single-layer structure and the multi-layer structure in the embodiments of the present invention.
[0034] Figure 8 This is a schematic diagram illustrating the absorption principle of terahertz waves within the multilayer structure in an embodiment of the present invention. Detailed Implementation
[0035] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0036] This embodiment provides a Ti3C2T-based... x Multilayer wave-shaped terahertz wave super-absorbing material, its structure is as follows Figure 1 As shown, a three-layer fabric structure is adopted, consisting of a high-load fabric layer, a low-load fabric layer, and a zero-load fabric layer from bottom to top; among which, Ti3C2T x Ti3C2T is a type of two-dimensional transition metal carbide / nitride MXene. Compared to other MXenes, it... x It has advantages such as high conductivity, high yield, and low cost; the flexible fabric is made of cotton yarn with a length of 50 ≤ mm, a width of 50 ≤ mm, a thickness of 0.29 mm ≤ 0.32 mm; the multilayer wave-type terahertz wave super-absorbing material is prepared by the following steps:
[0037] Step 1: Preparation of Ti3C2T x The suspension process is as follows:
[0038] Step 1.1: Mix hydrofluoric acid, hydrochloric acid and deionized water evenly to obtain an etching solution, wherein the mass percentage of hydrofluoric acid is 49 wt% and the mass percentage of hydrochloric acid is 38 wt%; the volume ratio of hydrofluoric acid, hydrochloric acid and deionized water is 5:12:24.
[0039] Step 1.2: Ti3AlC2 powder is slowly and uniformly added to the etching solution and stirred at an ambient temperature of 35°C for 24 hours to selectively etch away the Al layer in Ti3AlC2, thereby obtaining an acidic mixture of Ti3C2Tx; wherein, 1g of Ti3AlC2 powder requires 20.5ml of etching solution.
[0040] Step 1.3: Add deionized water to the acidic mixture of Ti3C2Tx and centrifuge and wash repeatedly until the pH of the supernatant is 5.5-6.5; filter the mixture and collect the lower precipitate for freeze drying for 12 hours to obtain multilayer Ti3C2Tx powder;
[0041] Step 1.4: Mix solid lithium chloride (LiCl) powder with deionized water to obtain an intercalation solution, wherein 1g of lithium chloride powder is dissolved in every 40ml of deionized water;
[0042] Step 1.5: Disperse the multilayer Ti3C2Tx powder in the intercalation solution (added at a uniform rate) and stir at 35°C for 4 hours; then add deionized water to the mixture and centrifuge and wash repeatedly until the supernatant turns black. Filter the mixture to obtain the lower layer of few-layer / monolayer Ti3C2Tx precipitate; each 1g of Ti3AlC2 powder requires 40ml of intercalation solution.
[0043] Step 1.6: Disperse the Ti3C2Tx precipitate in deionized water to obtain a uniformly dispersed Ti3C2Tx suspension; wherein the mass concentration of Ti3C2Tx in the suspension is 1 mg / ml to 16 mg / ml, and in this example, a high concentration of Ti3C2Tx is obtained. x The dispersion is 4 mg / ml, low concentration of Ti3C2T x The dispersion concentration was 1 mg / ml.
[0044] Step 2: Pre-clean the soft fabric with anhydrous ethanol and dry it for later use; this is the zero-load fabric layer. The soft fabric has dimensions of 50mm in length, 50mm in width, and approximately 0.29–0.32mm in thickness. Soak the gauze separately in a high-concentration Ti3C2T solution. x Dispersion, low concentration Ti3C2T x In the dispersion, the fabric is repeatedly and thoroughly rolled with rollers to ensure that it is fully adsorbed and filled; then the treated fabric is taken out and left to dry at room temperature for 6 hours to obtain high-load fabric layer and low-load fabric layer respectively.
[0045] Step 3: Stack the multiple layers of fabric in the order of high-load fabric layer, low-load fabric layer and zero-load fabric layer from bottom to top to obtain a three-layer fabric structure;
[0046] Step 4: Mix waterborne polyurethane and deionized water evenly to obtain a waterborne polyurethane dispersion, wherein the volume ratio of waterborne polyurethane to deionized water is 1:9; immerse the three-layer fabric structure in the waterborne polyurethane dispersion, and use rollers to roll it to remove air between the fabrics. Then remove the three-layer fabric structure and fold it several times at intervals of 8-10 mm. After that, let it stand at room temperature for 6 hours to complete the drying, thus obtaining the Ti3C2T-based product. x Multilayer wave-shaped terahertz wave super-absorbing material.
[0047] This embodiment first discusses the above-mentioned Ti3C2T-based... x The structure of the multilayer wave-type terahertz wave super-absorbing material was described, and the results are as follows: Figures 1-2 As shown; where, Figure 1 As shown in the figure, the main body of the multilayer structure is composed of fabrics with different concentration loads, and a layer of waterborne polyurethane-WPU is wrapped around the main body structure. Figure 2 The figures show schematic diagrams and sample images of smooth and wavy multilayer structures. As can be seen, the different shapes of the multilayer structures result in different reflection effects on incident waves. The smooth multilayer structure reflects the incident wave only once, exhibiting specular reflection, while the wavy multilayer structure achieves multiple reflections of the incident wave, exhibiting diffuse reflection. This embodiment then discusses the above-mentioned Ti3C2T-based... x A comparative test was conducted on a multi-layered wavy terahertz wave super-absorbing material, as well as high-load fabric layers, low-load fabric layers, zero-load fabric layers, and non-wavy multi-layered fabric structures. The results are as follows: Figures 3-7 As shown. Among them, Figure 3 The figure shows the structural strength test diagram of the multilayer wave-type terahertz wave super-absorbing material in an embodiment of the present invention. As can be seen from the figure, the material can support the weight of a mobile phone. Figure 4 The images shown are scanning electron microscope (SEM) test images of single-layer and multi-layer structures in embodiments of the present invention. (a) is a zero-load fabric, (b) is a low-load fabric, (c) is a high-load fabric, and (d) is a multi-layer structure. Figure 4 (a)(b)(c) It can be seen that Ti3C2T x In fabrics, Ti3C2T mainly exists in three forms: adhesion, suspension, and film formation. Furthermore, as the concentration increases, Ti3C2T... x The content of [something] increased significantly; in addition, [something] was caused by [something]. Figure 4 (d) It can be seen that a layer of WPU is attached to the surface of the multilayer structure. This protective layer not only plays the role of adhesion and coating, but also greatly increases the structural strength of the material. Figure 5The graph shows a comparison of the reflectance of single-layer and multi-layer structures. As can be seen from the graph, for the single-layer structure, the reflectance increases with increasing concentration. This is because as the load increases, more conductive pathways are formed on the fabric surface, and the skin effect becomes more pronounced. The reflectance of the multi-layer structure is slightly greater than that of the single-layer structure with zero concentration load. This is because a small portion of the terahertz waves incident on the multi-layer structure are reflected back. The reflectance of the wavy multi-layer structure is slightly lower than that of the flat non-wavy multi-layer structure. This is because the wavy shape provides multiple opportunities for reflection and incident, changing from specular reflection to diffuse reflection, thus reducing the overall reflectance of the material to the outside world. Figure 6 The figure compares the electromagnetic shielding effectiveness of single-layer and multi-layer structures. As can be seen, for the single-layer structure, the electromagnetic shielding effectiveness increases with increasing concentration. This is because, with increasing load, the incident terahertz wave decreases, and the fabric fibers cover more Ti3C2 nanosheets, providing more electrical losses. The electromagnetic shielding effectiveness of the multi-layer structure is significantly better than any single-layer structure, and the electromagnetic shielding effectiveness of the wavy multi-layer structure is higher than that of the non-wavy type. Figure 7 The figure shows a comparison of the absorption resistance (RL) values for single-layer and multi-layer structures. As can be seen, in this embodiment, the RL of the multi-layer structure is greater than that of the single-layer structure, meaning the absorption performance of the multi-layer structure is significantly higher. This is because the single-layer structure cannot simultaneously achieve impedance matching and attenuation characteristics, resulting in relatively weak absorption performance. The multi-layer structure effectively combines the characteristics of single-layer structures under different loads, achieving a superior absorption effect. Furthermore, compared to non-wave-shaped multi-layer structures, wave-shaped multi-layer structures have lower reflectivity, higher electromagnetic shielding effectiveness, and stronger absorption of terahertz waves, thus resulting in a higher RL value. Finally, this embodiment further elaborates on the above-mentioned Ti3C2T-based... x The absorption principle of multilayer wave-type terahertz wave super-absorbent materials was explained, and the results are as follows: Figure 8 As shown in the figure, the material absorbs waves mainly through two pathways: on the one hand, the Ti3C2 nanosheets covering the fiber surface form a good conductive path, and the terahertz wave induces a current on it, converting electromagnetic energy into heat energy to achieve energy attenuation; on the other hand, the incident wave generates multiple reflections and scatterings between the Ti3C2 nanosheets, and energy attenuation is achieved through this process.
[0048] In summary, this invention provides a Ti3C2T-based... x Multilayer wave-shaped terahertz wave super-absorbing material, using different Ti3C2T xThe multi-layered fabric structure, which combines load capacity, takes into account both impedance matching and loss absorption. At the same time, the wave-shaped shape changes the reflection properties of terahertz waves on the surface, changing it from specular reflection to diffuse reflection, thereby reducing the material's reflectivity to the outside world. It has excellent electromagnetic wave absorption performance in the 0.3–1.2 THz frequency band. In addition, because the material has strong structural stability, low manufacturing cost, and simple preparation method, it is feasible for large-scale production and application.
[0049] The above description is merely a specific embodiment of the present invention. Any feature disclosed in this specification may be replaced by other equivalent or similar features unless otherwise specified. All disclosed features, or steps in all methods or processes, may be combined in any way except for mutually exclusive features and / or steps.
Claims
1. A Ti3C2T-based x The multilayer wave-shaped terahertz wave super-absorbing material is characterized by, The terahertz wave super-absorbent material consists of a multi-layered fabric structure and an outer layer of water-based polyurethane (WPU). The multi-layered fabric structure is composed of multiple layers of flexible fabric, with each layer of flexible fabric adsorbed and filled with a corresponding loading amount of Ti3C2T. x Following the bottom-up order, Ti3C2T on the flexible fabric x The load decreases layer by layer until it reaches zero; the multi-layered fabric structure presents a wavy, undulating shape.
2. The Ti3C2T based invention as described in claim 1 x The multilayer wave-shaped terahertz wave super-absorbing material is characterized by, The flexible fabrics include: cotton gauze, non-woven fabric, grey fabric, and dust-free cloth.
3. The Ti3C2T based invention as described in claim 1 x A method for preparing multilayer wave-type terahertz wave super-absorbing materials, characterized in that... Includes the following steps: Step 1: Use an acidic etching solution to etch Ti3C2T x The precursor Ti3AlC2 was selectively etched, and the reaction product was centrifuged, washed, and freeze-dried to obtain multilayer Ti3C2T. x Powder; multilayer Ti3C2T x The powder was placed in an intercalation solution for intercalation treatment, and the reaction product was centrifuged and washed to obtain Ti3C2T. x The precipitate was then dispersed in deionized water to obtain a predetermined concentration of Ti3C2T. x suspension; Step 2: Pre-clean and dry the flexible fabric with anhydrous ethanol to obtain a zero-load flexible fabric; immerse the flexible fabric in Ti3C2T x The fabric is placed in a suspension and rolled multiple times on both sides using rollers. After being removed, it is left to dry at room temperature to obtain a flexible fabric with a preset load. Step 3: According to Ti3C2T x The load is gradually reduced from bottom to top until zero, and multiple layers of flexible fabric are stacked to form a multi-layer fabric structure. Step 4: Immerse the multi-layered fabric structure in an aqueous polyurethane dispersion and roll it with rollers to remove air between the multiple layers of flexible fabric. After removal, fold it several times to form a wavy shape, and then let it dry at room temperature to obtain the Ti3C2T-based structure. x Multilayer wave-shaped terahertz wave super-absorbing material.
4. The Ti3C2T based invention as described in claim 3 x A method for preparing multilayer wave-type terahertz wave super-absorbing materials, characterized in that... In step 1, the acidic etching solution is obtained by uniformly mixing hydrofluoric acid, hydrochloric acid and deionized water, wherein the mass percentage of hydrofluoric acid is 49 wt% and the mass percentage of hydrochloric acid is 38 wt%; the volume ratio of hydrofluoric acid, hydrochloric acid and deionized water is 5:12:
24.
5. The Ti3C2T based invention as described in claim 3 x The preparation method of the multilayer wave-type terahertz wave super-absorbing material is characterized by, In step 1, the intercalation solution is obtained by mixing solid lithium chloride (LiCl) powder with deionized water, wherein 1g of lithium chloride powder is dissolved in every 40ml of deionized water.
6. The Ti3C2T based invention as described in claim 3 x The method for preparing multilayer terahertz wave super-absorbent materials is characterized by, In step 1, each 1g of precursor Ti3AlC2 corresponds to 20.5ml of etching solution; each 1g of precursor Ti3AlC2 corresponds to 40ml of intercalation solution.
7. The Ti3C2T based invention as described in claim 3 x The preparation method of the multilayer wave-type terahertz wave super-absorbing material is characterized by, In step 2, the dimensions of the flexible fabric are: length 50≤mm, width 50≤mm, thickness 0.29mm≤0.32mm.
8. The Ti3C2T based invention as described in claim 3 x A method for preparing multilayer wave-type terahertz wave super-absorbing materials, characterized in that... In step 2, the number of single-sided rolling cycles is ≥10.
9. The Ti3C2T based invention as described in claim 3 x The preparation method of the multilayer wave-type terahertz wave super-absorbing material is characterized by, In step 4, the number of rolling cycles is ≥10, and the folding interval is 8-10mm.
Citation Information
Patent Citations
Wave type carbon felt electromagnetic shielding structural body and preparation method thereof
CN109263172A
Integrated impedance gradient flexible wave-absorbing material and preparation method thereof
CN112538761A